Covid-19 Containment Communication in Nigeria: Do Kari-Kasa Community Still Believe ‘the Media are of the Devil’? - Kamoru Aremu Salaudeen; Umar Olansile Ajetunmobi; Ayobami Ojebode (CV. Literasi Indonesia, 2022)
The Covid-19 pandemic created an atmosphere of global uncertainty that challenged established assumptions and ways of life. Amid the uncertainty, most people turned to mass and social media for updates, direction and, especially during lockdowns, companionship. An earlier study of the Kari-kasa community shows their total disdain for modernity including the mass media: radio, television and newspaper. The question then arises: was the Kari-kasa able to sustain this disdain during a pandemic that turned most people to the media? To what extent did the community uphold its aversion to modernity in the face of a crippling pandemic? Employing classical ethnographic field methods of focus group discussion (FGD), observation, in-depth and key informant interviews, this study established a reasonable level of Covid-19 awareness among the Kari-kasa members, some of whom seemed to be modifying their belief system to conform to social pressure. They largely declined Covid-19 safety rules believing it was not obligatory. The nature of their information-seeking behavior breeds information disorder and infodemic within their micro-community. The Kari-kasa appeared to be left behind in government efforts on Covid-19 containment communication interventions. It is therefore recommended that specific behavior change communication intervention be targeted at conservative marginal and hidden communities such as Kari-kasa just like it is for the Amish. Also, since Kari-kasa members exhibit ideological belief rather than behavioral belief explained in theory, behavior change interventions targeted at such groups should pay attention to this influential factor for the intervention to be compatible with their belief.